1973
DOI: 10.1111/j.1471-4159.1973.tb00287.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Dna Synthesis and Nuclear Proteins in the Cerebrum and Cerebellum of 8‐day‐old Rats

Abstract: In‐8‐day‐old rats the higher rate of DNA replication in cerebellum than in cerebrum is accompanied by an enhanced synthesis of nuclear proteins. The greatest difference between the incorporation of tritiated leucine into proteins of cerebral and cerebellar cell nuclei occurs in the acid‐soluble deoxyribonucleoproteins. However, the specific radioactivity of the acidic deoxyribonucleoproteins is similar in both tissues. The relative content of these proteins and the activity of the RNA polymerase is higher in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

1975
1975
1982
1982

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
1
0
1
Order By: Relevance
“…The Mn2'/(NH,),S0, stimulated reaction is greater in cerebellar nuclei during the first period of postnatal development, especially at 5 days of age, than in the other regions. This result is different from those obtained by BURDMAN et al (1973), who found a lower RNA polymerase activity in cerebellum of young rats. Possibly, this difference can be explained by the different yield of big neuronal and astrocytic nuclei during the purification procedure or by the different conditions of the assay of RNA polymerase activity.…”
Section: Resultscontrasting
confidence: 99%
“…The Mn2'/(NH,),S0, stimulated reaction is greater in cerebellar nuclei during the first period of postnatal development, especially at 5 days of age, than in the other regions. This result is different from those obtained by BURDMAN et al (1973), who found a lower RNA polymerase activity in cerebellum of young rats. Possibly, this difference can be explained by the different yield of big neuronal and astrocytic nuclei during the purification procedure or by the different conditions of the assay of RNA polymerase activity.…”
Section: Resultscontrasting
confidence: 99%
“…1. Finally, it was clearly demonstrated that in both the 8-day-old (Burdman et al, 1973) and the adult rat (McEwen et al, 1972) the capacity for RNA synthesis per nucleus (i.e., per unit of DNA) was several times higher in the cerebrum than in the cerebellum, a result to be expected from our findings (see Fig. 3).…”
Section: Isc Uss I0 Nsupporting
confidence: 83%